Determinants of ethical risk sensitivity amongst accounting and business students in NTU. - Chua, Sze Chyi. (2008)
This research study focuses on finding the determinants of ethical risk sensitivity amongst accounting and business students in NTU. Analysis is done to find the effects of gender, ethical education and work experience on the level of ethical risk sensitivity on these two groups of students.